Assessment of Pain, Acceptance of the Disease, Adaptation to Life and Strategies for Coping with the Disease among Patients with Ovarian Can-cer - Urszula Religioni; Aleksandra Czerw; Michał Piotr Budzik; Andrzej Deptała; Anna Maria Badowska-Kozakiewicz (Tehran University of Medical Sciences, 2021)
No Abstract